Post-Operative Radiotherapy for Soft Tissue Sarcoma of the Anterior Compartment of the Thigh: Should the Sartorius Muscle be Included?. (2005) - Barnett, Gillian C.; Hoole, Andrew C. F.; Twyman, Nicola; Jefferies, Sarah J.; Burnet, Neil G.
Abstract : Purpose: The clinical target volume (CTV) of post-operative radiotherapy for soft tissue sarcoma of the limbs conventionally includes the whole of the transverse cross-section of the affected anatomical compartment. In the anterior thigh sartorius appears to lie within its own fascial compartment and can be safely excluded. We investigated the potential impact of omitting sartorius from the anterior muscle compartment on patients with soft tissue sarcoma of the thigh. Patients and methods: We used the planning CT data from six patients who had previously received post-operative radiotherapy for soft tissue sarcoma of the thigh. The anterior compartments were outlined twice, initially including and then excluding the sartorius muscle. The volumes of the anterior compartment (i.e., the CTVs), both with and without sartorius, and the corresponding planning target volumes (PTVs) were calculated. Treatment plans were prepared for each PTV. For both volumes the unirradiated normal tissue corridor was outlined on each CT slice. The volume and circumference of the unirradiated corridor were then calculated. Results: For all six patients there was an important improvement in normal tissue sparing by excluding sartorius. The mean reduction in volume of the anterior compartment when sartorius was excluded was 10% (95% Confidence Interval 8–12%), whilst the mean decrease in PTV was 11% (95% CI 7–14%). There was a substantial increase in the volume of the unirradiated normal tissue corridor, with a mean value of 77% (95% CI 41–114%) when sartorius was excluded. In addition, the percentage increase in the size of the unirradiated normal tissue corridor, expressed as a percentage of the whole leg circumference, was 10% (95% CI 8–13%). When sartorius was included in the anterior compartment, the circumference of the unirradiated corridor was less than one-third of the whole leg circumference in four of the six patients. When sartorius was excluded, the circumference of the unirradiated corridor was greater than one-third of the leg circumference over the entire length of the target volume in all patients. Discussion: It is essential to know the anatomy of the sartorius muscle to be able to exclude it from the anterior compartment. The increase in the size of the normal tissue corridor when sartorius is excluded should deliver clinical advantage by decreasing the normal tissue adverse effects.